Preparation and Characterization of Alginate and Psyllium Beads Containing Lactobacillus acidophilus. (2nd May 2012) - Lotfipour, Farzaneh; Mirzaeei, Shahla; Maghsoodi, Maryam
Abstract : This paper describes preparation and characterization of beads of alginate and psyllium containing probiotic bacteria of Lactobacillus acidophilus DMSZ20079. Twelve different formulations containing alginate (ALG) and alginate-psyllium (ALG-PSL) were prepared using extrusion technique. The prepared beads were characterized in terms of size, morphology and surface properties, encapsulation efficiency, viabilities in acid (pH 1.8, 2 hours) and bile (0.5% w/v, 2 hours) conditions, and release in simulated colon pH conditions. The results showed that spherical beads with narrow size distribution ranging from1.59 ± 0.04 to1.67 ± 0.09 mm for ALG and from1.61 ± 0.06 to1.80 ± 0.07 mm for ALG-PSL with encapsulation efficiency higher than 98% were achieved. Furthermore, addition of PSL into ALG enhanced the integrity of prepared beads in comparison with ALG formulations. The results indicated that incorporation of PSL into alginate beads improved viability of the bacteria in acidic conditions as well as bile conditions. Also, stimulating effect of PSL on the probiotic bacteria was observed through 20-hour incubation in simulated colonic pH solution. According to our in vitro studies, PSL can be a suitable polymer candidate for partial substitution with ALG for probiotic coating.